Neural Network Development in Late Adolescents during Observation of Risk-Taking Action - Tamura, Miyuki; Moriguchi, Yoshiya; Higuchi, Shigekazu; Hida, Akiko; Enomoto, Minori; Umezawa, Jun; Mishima, Kazuo (PLOS ONE, 2012)
Emotional maturity and social awareness are important for adolescents, particularly college students beginning to face the challenges and risks of the adult world. However, there has been relatively little research into personality maturation and psychological development during late adolescence and the neural changes underlying this development. We investigated the correlation between psychological properties (neuroticism, extraversion, anxiety, and depression) and age among late adolescents (n = 25, from 18 years and 1 month to 22 years and 8 months). The results revealed that late adolescents became less neurotic, less anxious, less depressive and more extraverted as they aged. Participants then observed video clips depicting hand movements with and without a risk of harm (risk-taking or safe actions) during functional magnetic resonance imaging (fMRI). The results revealed that risk-taking actions elicited significantly stronger activation in the bilateral inferior parietal lobule, temporal visual regions (superior/middle temporal areas), and parieto-occipital visual areas (cuneus, middle occipital gyri, precuneus). We found positive correlations of age and extraversion with neural activation in the insula, middle temporal gyrus, lingual gyrus, and precuneus. We also found a negative correlation of age and anxiety with activation in the angular gyrus, precentral gyrus, and red nucleus/substantia nigra. Moreover, we found that insula activation mediated the relationship between age and extraversion. Overall, our results indicate that late adolescents become less anxious and more extraverted with age, a process involving functional neural changes in brain networks related to social cognition and emotional processing. The possible neural mechanisms of psychological and social maturation during late adolescence are discussed.